TINJAUAN EKONOMI SYARIAH TERKAIT DAMPAK DARI KENAIKAN TARIF PDAM DI KOTA JAMBI - Firdawati Firdawati; Ambok Pangiuk; Marissa Putriana (Jurnal Kajian dan Penalaran Ilmu Manajemen, 2024)
The method used by the author in this study is a qualitative method, this method is used to observe, understand and describe a study about the increase in tariffs for PDAM Tirta Mayang in Jambi city. The drinking water tariff is the cost of drinking water services that must be paid by the customer for each use of drinking water provided by the organizer. In the Regulation of the Minister of Home Affairs Number 23 of 2006 concerning Technical Guidelines and Procedures for Determining Drinking Water Tariffs at Regional Drinking Water Companies (PDAMs). The tariff for the level of basic drinking water needs must be affordable by customers whose purchasing power is equal to or less than the Provincial Minimum Wage. In the event that household expenditures to meet basic drinking water standards do not exceed 4% (four percent) of the income of the customer community, the tariff meets the affordability criteria. Tariffs must be applied fairly. the calculation and determination of drinking water tariffs is based on the principles of affordability and fairness. Quality of service, full cost recovery, efficiency of water use, transparency, accountability and protection of raw water.